At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Given:
f(x)=x^2
g(x)=x-1
Find f(g(2))+g(f(-1))


Given Fxx2 Gxx1 Find Fg2gf1 class=

Sagot :

Answer:

-1

Step-by-step explanation:

First, we need to work out the left-hand side.

  • find g(2) → g(2) = 2 - 1 which is 1
  • next, find f(1) → f(1) = 1³ which is 1

Now, we can work out the right hand side.

  • find f(-1) → f(-1) = -1³ which is -1
  • then, find g(-1) → g(-1) = -1 - 1 = -2

Finally we can work out the full sum: 1 + -2 = -1.

Hope this helps!

Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.